A combined, adaptive strategy for managing evacuation routes. (May 2019) - Wu, Wen-Xiang; Huang, Hai-Jun
Highlights: Study freeway evacuation problems with limited inputs. Establish the optimal conditions for InFO strategy. Develop a combined evacuation strategy based on simple rules. Abstract: In this paper, we propose an intuitive, non-anticipative, partially decentralized, and adaptive combined strategy for managing evacuation routes with limited inputs so as to minimize the system clearance time. This strategy is intuitive due to the use of simple and transparent rules, non-anticipative because it relies on readily available information only, partially decentralized because only the upstream ramps are coordinately optimized, and adaptive due to the self-renewal with traffic condition. It is a combined strategy because it may include priority control strategy or proportional control strategy. Our approach is robust in the sense that it can be easily implemented, and can deal with not only real-time data but also predictive information. Numerical results show that the proposed strategy works effectively and can serve as a simple evacuation tool for regulating ramp discharge flows.